Analisis Pengaruh Tingkat Pengangguran dan Tingkat Pertumbuhan Penduduk Terhadap Tingkat Kemiskinan di Provinsi Jawa Barat - Chantika Putri Restiani; Siti Rahma; Deris Desmawan (Jurnal Ekonomi, Bisnis dan Manajemen, 2022)
The purpose of this study is to ascertain whether the population growth rate and unemployment rate have an impact on the poverty rate in West Java. Population growth and the unemployment rate are the independent variables, followed by the poverty rate as the dependent variable. The time series data used in this study include the years 2019 through 21. Multiple regression using SPSS 25.0 is the analytical approach employed. Where the regression equation, Y = 41,491 + 9,385 X1 + 14,239 X2, is discovered. This demonstrates that the poverty rate in the province of West Java has a unidirectional relationship with both the unemployment rate and population growth. The T test results showed that there was no relationship between West Java's poverty level and the unemployment rate. Additionally, the West Javan poverty rate is unaffected by the population growth variable. The F test indicates that the independent factors collectively have an impact on the dependent variable. The poverty rate is affected by the unemployment rate and population growth to the tune of 7.7%, with other factors affecting the remaining 92.3%.